2017
DOI: 10.5194/nhess-17-2245-2017
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami evacuation plans for future megathrust earthquakes in Padang, Indonesia, considering stochastic earthquake scenarios

Abstract: Abstract. This study develops tsunami evacuation plans in Padang, Indonesia, using a stochastic tsunami simulation method. The stochastic results are based on multiple earthquake scenarios for different magnitudes (M w 8.5, 8.75, and 9.0) that reflect asperity characteristics of the 1797 historical event in the same region. The generation of the earthquake scenarios involves probabilistic models of earthquake source parameters and stochastic synthesis of earthquake slip distributions. In total, 300 source mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 65 publications
0
15
0
1
Order By: Relevance
“…Previously, on February 10, 1797, and November 24, 1833, tsunami was reported with a respectively 5 m and 3-4 m inundation high of tsunami [3]. Padang is predicted to face up to 15 m tsunami inundation shortly [7], [8], [9], [3]. McCloskey reported that an accumulation of a vast seismic moment deficit since 1797 and 1833 at the megathrust [3].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, on February 10, 1797, and November 24, 1833, tsunami was reported with a respectively 5 m and 3-4 m inundation high of tsunami [3]. Padang is predicted to face up to 15 m tsunami inundation shortly [7], [8], [9], [3]. McCloskey reported that an accumulation of a vast seismic moment deficit since 1797 and 1833 at the megathrust [3].…”
Section: Introductionmentioning
confidence: 99%
“…Dalam perencanaan mitigasi bencana tsunami sistem evakuasi memegang peranan penting dalam meminimalkan risiko kehilangan jiwa manusia (Dewi, 2012;Muhammad et al, 2017). Fasilitas dan tempat evakuasi harus tersedia di daerah rawan bencana.…”
Section: Pendahuluanunclassified
“…McCloskey [3] reported that on February 10, 1797, and November 24, 1833, two earthquakes triggered a tsunami of 5 m and 3-4 m inundation high respectively. Furthermore, McCloskey and other scientists also predicted a huge seismic moment deficit accumulation since 1797 and 1833 at the megathrust which was predicted to trigger a 15 m tsunami inundation in Padang in the near future [3,6,7,8].…”
Section: Introductionmentioning
confidence: 99%